Knowledge, attitude, and practice of frailty management among clinical nurses: a cross-sectional study - Xueyan Huang; Haifang Zhou; Ying Feng; Mengchi Li; Rui Wang; Ge Fang; Lumeng Lu; Jian’ao Chen; Wenhui Jiang (BMC Geriatrics)
Abstract Background Frailty is a leading risk factor of falls, incapacitation, functional decline, and even death in aging populations globally. Clinical nurses play pivotal roles in screening, prevention, and intervention to reverse or slow the progression of frailty. The present study aimed to (1) understand the extent and influencing factors of knowledge, attitudes, and practices of clinical nurses for managing frailty, (2) elucidate the relationships of the knowledge, attitudes, and practices of clinical nurses for frailty management. Methods This cross-sectional study was conducted from March to April 2024 on 524 clinical nurses in a tertiary hospital in Zhejiang Province, China. The survey instruments included a questionnaire inquiring about the knowledge, attitudes, and practices of nurses in terms of frailty management, a demographic data form, and a self-designed frailty educational information questionnaire. Data were analyzed by descriptive statistics, univariate analysis, multiple linear regression, and structural equation modeling. Results Of 524 nurses, Only 37.2% were rated as good in terms of knowledge, attitude, and practice of frailty management, while 55.7% were rated as moderate. Among them, the proportion of nurses with good knowledge (10.3%) and practical skills (13.4%) is much lower than their attitude (65.3%). Structural equation modeling found that knowledge and attitudes were related to frailty management practices, with significant associations between knowledge and practices(β = 0.499, p < 0.001). Of the total effect size of knowledge influencing practice (total effect = 0.624, 95% CI: 0.455,0.791), approximately 20.0% was mediated by attitudes (indirect effect = 0.125, 95% CI: 0.076,0.187). Multiple linear regression analysis showed that age, organizational support, familiarity with relevant guidelines, familiar with the term frailty, and department all had a significant effect on the total score(adjusted R2 = 0.264, p < 0.001). Conclusions Despite inadequate knowledge and limited experience in frailty management, clinical nurses’ attitudes towards frailty management were positive, indicating potential for improvement. The model was useful to explain practices in frailty management, thereby providing a theoretical basis for development of targeted training programs. Clinical trial number Not applicable.